Analisa keberhasilan produk pakaian asal Jepang: Eksistensi brand Uniqlo di Indonesia - Shifra, Nasya Faza Cahya (Nur Science Institute, 2023)
The halal industry is a sector that has developed very rapidly. Its development was followed by an increasingly advanced era of globalization so that its existence can be recognized by the whole world. Opportunities that the halal industry gets are not only in Muslim countries, but non-Muslim countries are also taking part in getting these benefits and attention. Japan is a non-Muslim majority country, Japan is doing business by expanding to Indonesia which aims to penetrate the Indonesian market. The research method carried out by researchers is by means of library research and qualitative methods with secondary data. Where in this study using data originating from literature and supported by some secondary data. The results and the conditions explained by the researchers are related to the strategy carried out by Japan with the UNIQLO brand in providing Muslim-friendly clothing. In penetrating the market and its existence, Japan and UNIQLO have used many ways to attract the attention of the Indonesian people. The strategy in penetrating the Indonesian market carried out by Japan is by bringing the Cool Japan concept and the strategy in penetrating Muslim communities with Muslim friendly clothing is by collaborating with well-known designer Hana Tajima.